Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Prestasi Kerja Pegawai Di Puskesmas Wawo Kabupaten Bima - Ahmad Kadafi; Mulyadin Mulyadin (Pusat Riset dan Inovasi Nasional, 2023)
The importance of the existence of human resources in organizations originates from the increasing need for human resources functions for the implementation and development of organizations. The human resources function originates from the management function and strategic function. Organizations view it as important to make efforts to develop human resources because currently employees are a very important asset in achieving the stated goals of an organization. Human resource development is an activity related to increasing employee skills for sustainable growth within the organization. Human resource development is important to improve employee performance.